Design of a Virtual Laboratory for Practical Learning of Environmental Management and Industrial Safety - Ron-Valenzuela, Pablo (2022)
At present, the world has experienced great and serious problems with the arrival of the COVID-19 pandemic and, of course, among the sectors that present the most inconveniences is face-to-face university education; therefore, higher education centers seek teaching methodologies to put students into practice. For this reason, the creation and implementation of the virtual laboratory is an alternative solution to this problem; For this, technical criteria were proposed that were evaluated through weighted factors and the analysis of three alternatives that can contribute to the design of the virtual laboratory was carried out; these are Second life, Unity 3D and Virtual plant, selecting the most appropriate tool that responds to the needs of use. Unity 3D is the tool that best contributes to each of the proposed criteria, obtaining a virtual environment for practical learning of students through a virtual tour of a simulated industrial company for the artisan manufacture of chocolates with the SKETCHUP tool, during their journey through an avatar in the company the student interacts and finds questions based on the actual exposure of the avatar to occupational hazards and the environmental management that must be fulfilled within the company with response options based on knowledge learned in class, thus achieving content feedback and decision-making in the face of physical and environmental occupational risks.